Students’ Perception on Ideas' Role in Film Story Scenario Writing Learning - Bahren Bahren; Syahrul Ramadhan; Mezia Kemala Sari; Hermawati Syarief (STAI Hubbulwathan Duri, 2023)
This study aims to know the extent of students' perceptions of the importance of ideas in writing a film screenplay. The research approach uses a qualitative descriptive method. Data were collected through observation and questionnaires. The participants are fifth-semester students, as many as 42 people in the audio-visual class. The data were analyzed through three stages, namely data reduction, data presentation and conclusion. The results of data analysis found that most of the students, or 87.3%, students knew what ideas were in writing film scenarios. In addition, it was also found that ideas related to family are a concept that is considered by students as the easiest notion to write into scenarios. This is due to the proximity to the source of thought in writing. Meanwhile, the concept of tradition and traditional arts is an idea that is considered the most difficult for them to write because students lack experience and information related to tradition and art. The results of this study serve as a guide for teachers in developing students' ability to write film screenplays.